Novel management of sizeable calcaneal UBC with autograft and allograft amalgamation: a case report and review of literature - Mohanty, Tapas; Panchal, Sameer; Amin, Stavan; Gawhale, Sangeet; Talukder, Pritam (Journal of the Foot & Ankle, 2022)
Calcaneal unicameral bone cyst (UBC) is uncommon benign tumor that can be managed either conservatively or with different surgical interventions described in the literature. However, surgical intervention is usually preferred when the lesion is an active UBC significant in size, as there is the risk of pathological fracture due to thin bone, especially in load-bearing bones like the calcaneus. We report a case of calcaneal UBC considerable in size managed by open curettage and graft reconstruction using a combination of autograft and allograft in a 30-year-old male at two-years follow-up. Level of Evidence IV; Therapeutic Studies; Case Report.